Health Risk Appraisal: Two Decades of Change - Ellis, Lynda B.M. (1989)
At a 1989 health fair, 126 people evaluated the revised conversational, microcomputer-based University of Minnesota Health Risk Appraisal. Compared to a similar group who evaluated the original Appraisal approximately 10 years ago, there was no change in user-perceived helpfulness or motivation to change behavior. Approximately 90% of users receive at least some help from the appraisal and 21% probably or definitely intend to change behavior. It appears that the decreasing novelty of computer use over time does not influence user evaluation of the appraisal. Comparison with evaluation ratings given to a different health education package indicate that these ratings are specific to the appraisal and not a generalized response to any computer-based health education material.